Infant learning through games via Arduino - Lim, Ming Rui (2019)
For the healthy development of a child, it does not only include physical development domains but also emotional, behavioural, cognitive, language, and general learning competencies. The human brain undergoes rapid growth during childhood, driven in part by a child’s acquisition and integration of skills across many developments. It is important to foster the child’s development right from birth to ensure the healthy development of their sensory and cognitively. This report will cover in more in details the importance of development for children and also explain in details of what this project aims to achieve. This final year project includes the integration of both hardware and software where the author aims to build a prototype game puzzle that would effectively help the development of the child’s cognitive skills yet introduce fun to it.